THE EFFECTS OF CREATIVE ART ACTIVITIES INTEGRATED WITH SIMULATED SITUATIONS IN MULTI-AGE CLASSROOMS ON THE BASIC MATHEMATICAL SKILLS OF YOUNG CHILDREN. WAT PHRA KAEW SCHOOL, CHAI NAT PROVINCE - Amnouysan, Amonrat; Uthaipayuck, Dararat; Sinthunava, Kittiwan (Journal of Educational Review Faculty of Education in MCU, 2026)
The purpose of this research were to: 1) study the correlation of basic mathematical skills of young children before and after receiving creative art activities integrated with simulated situations in a multi-age classroom, and 2) compare the basic mathematical skills of young children before and after receiving creative art activities integrated with simulated situations in a multi-age classroom. This research was a quasi-experimental research using a one-group pretest-posttest design. The population consisted of four young children, boys and girls, studying in a multi-age classroom setting at Wat Phra Kaew School, Chai Nat Province, during the first semester of the academic year 2025. The group comprised two children from Kindergarten 2 and two children from Kindergarten 3. The research instruments included: The experience management plan based on creative art activities integrated with simulated situations for multi-age classroom, consisting of 32 plans. The Index of Item Objective Congruence (IOC) equal to 1.00, The Content Validity Index (IOC) for the Mathematics Basic Skills Test equal to 1.00. The test consisted of 4 sets, with 4 items each (16 items in total). The statistics used for data analysis were mean, standard deviation, and the Chi-square test. The research findings revealed that: 1) The basic mathematical skills of young children before and after receiving creative art activities integrated with simulated situations in a multi-age classroom were statistically significantly correlated at the statistically significant level of .05, and 2) The basic mathematical skills of young children after receiving the creative art activities integrated with simulated situations in a multi-age classroom were higher than before receiving the experiences, both overall and in each aspect.